Cardiac and Cerebellar Histomorphology and Inositol 1,4,5-Trisphosphate (IP3R) Perturbations in Adult Xenopus laevis Following Atrazine Exposure - Jaclyn Asouzu Johnson (MDPI AG, 2021)
Despite several reports on the endocrine-disrupting ability of atrazine in amphibian models, few studies have investigated atrazine toxicity in the heart and cerebellum. This study investigated the effect of atrazine on the unique Ca2+ channel-dependent receptor (Inositol 1,4,5-trisphosphate; IP3R) in the heart and the cerebellum of adult male Xenopus laevis and documented the associated histomorphology changes implicated in cardiac and cerebellar function. Sixty adult male African clawed frogs (Xenopus laevis) were exposed to atrazine (0 µg/L (control), 0.01 µg/L, 200 µg/L, and 500 µg/L) for 90 days. Thereafter, heart and cerebellar sections were processed with routine histological stains (heart) or Cresyl violet (brain), and IP3R histochemical localization was carried out on both organs. The histomorphology measurements revealed a significant decrease in the mean percentage area fraction of atrial (0.01 µg/L and 200 µg/L) and ventricular myocytes (200 µg/L) with an increased area fraction of interstitial space, while a significant decrease in Purkinje cells was observed in all atrazine groups (p < 0.008, 0.001, and 0.0001). Cardiac IP3R was successfully localized, and its mean expression was significantly increased (atrium) or decreased (cerebellum) in all atrazine-exposed groups, suggesting that atrazine may adversely impair cerebellar plasticity and optimal functioning of the heart due to possible disturbances of calcium release, and may also induce several associated cardiac and neural pathophysiologies in all atrazine concentrations, especially at 500 µg/L.